Gamification and AI for Engaging Risk Management Education : A Systematic Literature Review and an AI Chatbot Exemplifying Gamified Communication - Mäenpää, Mikael; Yli-Viitala, Pirjo; Arrasvuori, Juha (VAKKI communication research association, 2025)
Risk Management Education (RME) helps individuals and organisations to manage risks and make informed decisions. Yet it often feels abstract and difficultto engage with. The increasing complexity of modern risks calls for more interactive educational approaches. These approaches can help foster meaningful communicational relations between learners, technologies and insti-tutions in RME. Gamification and artificial intelligence (AI) offer one potential solution. This ar-ticle presents a Systematic Literature Review (SLR) of 18 studies on gamification and AI in RME using PRISMA guidelines,based on abstracts and validatedwith clusteringanalysisof full texts. Keywords, termsand entities were classified into categories to identifyconceptualgaps. Results indicated that gamified elements like simulations, scenarios, collaboration and feedbackcan support RME. AIin RMEappeared rarely and mostly conceptually, yet it shows potential for adaptive guidance and personalisation. IntegratedRME–gamification–AI approaches were scarce, revealing a research gap. To illustrate this case, we present Arvo, an AI-basedchatbot developed in parallel withthis research, informed bySLR findings and exemplifyinggamified communication for climate risk education. A research agenda is proposed for gamification and AI in RME, focusing on simulations, storytelling and AI chatbots to guide theory and practice.
Keywords: Artificial intelligence; Chatbot; Gamification; Risk management education; Systematic literature review; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|